2008
DOI: 10.1080/17408980701444718
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of a performance assessment procedure in ice hockey

Abstract: Background: Coaches and physical educators must obtain valid data relating to the contribution of each of their players in order to assess their level of performance in team sport competition. This information must also be collected and used in real game situations to be more valid. Developed initially for a physical education class context, the Team Sport Assessment Procedure (TSAP) is precisely an assessment procedure developed to measure the individual performance of each player in a game situation. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 20 publications
(31 reference statements)
1
36
0
8
Order By: Relevance
“…Nevertheless, the authors and/or collaborators have shown a strong tendency to apply the instrument to extra-curricular sports, because they assumed it would be accepted in PE. Hence, in almost one half of the works referring to the TSAP, it was used in organized sports (specifically, in ice hockey - Nadeau et al, 2008aNadeau et al, , 2008b.…”
Section: Assessment Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the authors and/or collaborators have shown a strong tendency to apply the instrument to extra-curricular sports, because they assumed it would be accepted in PE. Hence, in almost one half of the works referring to the TSAP, it was used in organized sports (specifically, in ice hockey - Nadeau et al, 2008aNadeau et al, , 2008b.…”
Section: Assessment Contextmentioning
confidence: 99%
“…The greater use of the TSAP for peer-assessment in comparison with the GPAI seems reasonable because the TSAP was especially developed for peer-assessment in order to make the process more active and formative (Gréhaigne et al, 1997;Richard et al, 1999). Various studies showed that the TSAP was valid for use by PE students between 14 and 17 years of age (Nadeau et al, 2008b) and from 11 to 14 years (Richard et al, 2000). As with the GPAI, Richard et al (2000) noted that when the TSAP is used by the students/players, it is not necessary to use all the component criteria, but instead, only the criteria that are more suitable to the students' capacity.…”
Section: Evaluatorsmentioning
confidence: 99%
“…While much of this work has focused on techniques for assessing the performances of school students in physical-activity contexts (e.g. Nadeau, Richard, and Godbout 2007;Oslin 2003) the conceptual bases for these assessment approaches have the potential to contribute to a more educationally defensible employment of assessment in higher-education kinesiology settings. Conceptual and empirical work on assessment in PE teacher education (PETE) is also of particular relevance to the broader kinesiology field as it attends to the cognitive and psychomotor competencies of students in the same phase of learning (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that each invasion game is context specific within the similar tactical concepts, the global feature of the GPAI may not always provide a valid and reliable assessment of game performance for various invasion games (Nadeau, Richard, & Godbout, 2007;Richard et al, 2000). Using the GPAI to measure individual players' game performance behaviors in soccer, basketball, and volleyball games, Oslin et al (1998) reported that in 66% of the cases, the GPAI game components could differentiate players' observable game behaviors and abilities.…”
Section: Needs For Elaborating On the Gpaimentioning
confidence: 99%